Răspuns :
9x²-6x+1=5
9x²-6x+1-5=0
9x²-6x-4=0
acum afla delta , x1 si x2 simplu de tot
9x²-6x+1-5=0
9x²-6x-4=0
acum afla delta , x1 si x2 simplu de tot
[tex]9x^2-6x+1=5\;\;\\
\rightarrow\;\;9x^2-6x+1=\underbrace{(3x)^2-2\cdot3x\cdot1+1^2=5}_{(3x-1)^2=5\;\rightarrow\;
3x-1=\pm\sqrt5}\\
.\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;x_{1;2}=\frac{1\pm\sqrt5}{3}[/tex]
Pentru ca imaginea sa se deschida mai repede , dati ,, refresh " !
Pentru ca imaginea sa se deschida mai repede , dati ,, refresh " !